2002
DOI: 10.1046/j.1365-246x.2002.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of earthquakes in the Upper Rhinegraben using empirical Green functions

Abstract: Summary In low seismicity areas such as southwestern Germany, quantitative statements on strong ground, motion suffer from the lack of instrumental strong motion data although the historic catalogue indicates that events of moment magnitudes up to MW= 6 are conceivable. This is the situation in the Upper Rhinegraben area were moderate earthquakes with low probability but high impact caused by the significant aggregation of population, infrastructure and industrial facilities are expected to happen. We have dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…The use of more than one EGF in order to reduce the possible effect of different location of the EGF and of the modelled event has been suggested, e.g. by Wössner et al (2002). Only those EGFs were combined whose correlation maximum exceeded 0.7 within a lag of ±2 sample intervals, otherwise the corresponding phase was not modelled.…”
Section: Modelling Of Multiple Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of more than one EGF in order to reduce the possible effect of different location of the EGF and of the modelled event has been suggested, e.g. by Wössner et al (2002). Only those EGFs were combined whose correlation maximum exceeded 0.7 within a lag of ±2 sample intervals, otherwise the corresponding phase was not modelled.…”
Section: Modelling Of Multiple Eventsmentioning
confidence: 99%
“…The EGF method has also been used for modelling large earthquakes (e.g. Hutchings 1991; Wössner et al 2002); the author is, however, not aware of any similar study of small earthquakes. This could have resulted from the fact that some researches observed an apparent breakdown in self‐similarity of earthquakes of magnitude less than about 3 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the method produces useful time histories. One other study by Wossner et al (2002) compared peak horizontal acceleration and response spectra in terms of spectral accelerations and peak horizontal accelerations with the attenuation laws proposed for Europe. Their results encouraged the application of the approach as a supplementary tool for site-specific ground motion prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These models are mostly explained as quasi-dynamics models (Boatwright 1981), which depend on field observations, laboratory experiments, and numerical modeling. The methodology has been validated several times (Hutchings and Wu 1990;Hutchings 1991;Heuze et al 1994;Hutchings 1994;Foxall et al 1996;Hutchings and Jarpe 1996;Hutchings et al 1997Hutchings et al , 1998Hutchings et al , 2007Jarpe and Kasameyer 1996;Rosset et al 1998;Wossner et al 2002;Scognamiglio and Hutchings 2009;Nicknam and Eslamian 2011;Golara and Jazany 2013;Papoulia et al 2015).…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Additionally, according to Wossner et al (2002), the number of EGFs affects the amplitude of synthesized seismograms. They found that when frequencies are higher than the source corner frequency, these amplitudes tend to be higher if a single EGF is used to interpolate records over the fault.…”
Section: Methodsmentioning
confidence: 99%